Western European Quaternary lions: new working hypotheses. (4th February 2013) - Masseti, Marco; Mazza, Paul P. A.
<x xml:space="preserve">Abstract</x> Cave lions (Panthera spelaea), which spread throughout Western Europe for several thousand years, disappeared approximately 14 000–14 500 years ago. They were supposedly replaced by modern lions (Panthera leo) approximately 8000 years ago. Modern lions reached the steppes of Ukraine and Hungary, without penetrating the forests of Central Europe. The present study focuses on Italian and Spanish findings that possibly bridge the alleged absence of these big cats from Europe for 6000 years. Fossil lion remains from reliably radiocarbon‐dated levels have been plotted against the δ18O curve and mapped. The accumulated evidence indicates that lions inhabited Western Europe uninterruptedly from the early Middle Pleistocene up to the Early Holocene. Moreover, all of the latest Pleistocene/early Holocene lion‐bearing localities do not range farther than the 44th parallel north and are located at relatively high altitudes. Two working hypotheses are formulated: one, which is less likely because it is not supported by palaeontological evidence indicating earlier migrations of lions from Africa, suggests that modern lions entered Western Europe prior to 8000 years ago; the second, which is more probable, suggests that P. spelaea (or an advanced offspring of the species) survived up until the latest Pleistocene. Panthera leo accessed Eastern Europe between 6000–6500 and 8000 years ago but was prevented from penetrating further west, probably because of the intrusive presence of their indigenous European relatives, and/or the increasing encroachment of modern human populations. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 66–77.